Influence of anthropometric measures on throwing power - Vuleta Jr., D. (Acta Kinesiologica, 2013)
The main purpose of this research was to determine if the anthropometric measures have a significant impact on throwing power of top level junior handball players. The correlation coefficients and the stepwise linear regression analyses were used to determine the relations between the anthropometric measures and the throwing power tests. The predictor group consisted of 11 variables of anthropometric measures and the criterion variables were the results scored in 4 different throwing power tests. Significant relations were determined between the anthropometric measures and throws from 4 meters from a sitting position (.2=0.63, p<0.02), standing throw from 6 meters (.2=0.81, p<0.01), and run up three step jump shot from 9 meters (.2=0.80, p<0.01).